Jumat Bersih: Strategi untuk Menguatkan Gotong Royong Siswa Sekolah Dasar melalui Proyek Profil Pelajar Pancasila - Maulina, Fourtina Okta; Indrakurniawan, Machful (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to describe the strengthening of mutual cooperation character education through the